Production of Lovastatin from crude glycerol via fermentation using aspergillus terreus ATCC 20542 Bernadeth S. Antonio. - Antonio, Bernadeth S. (2013)
Environmental and natural resources concerns, such as atmospheric pollution, increasing cost and depletion of fossil fuels led to development of alternative sources of petroleum-based fuels, including biodiesel. Increasing demand for biodiesel may result in increasing generation of waste or excess crude glycerol, which is usually part of wastewater streams. This research investigated the possibility of using crude glycerol to be a sole carbon source in lovastatin production using Aspergillus terreus ATCC 20542 in a shake flask fermentor and also in a 5-L fermentor system using the optimum condition found in the shake flask experiment. Lovastatin is commonly used in medicine to lower blood cholesterol specifically the low density lipoprotein (LDL) that is known as bad cholesterol. The effects of concentration of crude glycerol (10 g/L, 30 g/L and 50 g/L), implementing pre-culture prior to fermentation, different nitrogen sources and concentrations of N sources (yeast extract, ammonium sulfate and different forms of soya) at different incubation time on lovastatin and biomass yields and A. terreus ATCC 20542 growth and lovastatin production kinetics were determined. These were compared to those using pure glycerol. Results show that Aspergillus terreus ATCC 20542 grow in crude glycerol and produces lovastatin even without pre-culture. Implementing pre-culture improves the production of lovastatin. Lovastatin production increased as the concentration of crude glycerol decreased when pre-culture was implemented. The nitrogen source greatly affected the production of lovastatin. The lovastatin production from different N sources at decreasing order are as follows: different forms of soya (5.96 mg/L) > yeast extract (2.91 mg/L) > ammonium sulfate (1.33 mg/L).
Dissertation (Ph.D. Chemical Engineering)--University of the Philippines, Diliman
Keywords: Lovastatin; Glycerol; Fermentation